La Develización de la Estatua del Gran Héroe, quien se ofreció en holocausto en el altar de la patria para redimirla de la esclavitud: Juan Santamaría, 15 de setiembre de 1891 - Fumero Vargas, Patricia (2016)
This paper analyses the inauguration of the statue of the Costa Rican national hero Juan Santamaría on September 15, 1891. The objective of this paper is to contribute to the study of the construction of Costa Rican identities. First, I analyze the role of civic statuary and commemorations. Second, elements that promote identity formation are examined. Third, I consider the process that led to the official interest in the National Campaign of 1856-57 and the role played by the inauguration of Santamaría statue in the process.